(untitled) (Baghdad Science Journal, 2016)
The purpose of this study was to examine the role of cortisol, and it is related to BMI in the chronic diseases which may increase early cardiovascular disease (CVD) in old Iraqi. The subjects were 116 adults, aged 51-71 years. Body Mass Index (BMI), Waist Circumferences (WC) and Waist Hip Ratio (WHR) were used as a measure of adiposity. Investigation showed highly significant difference between patients in BMI ranges, most of male were in an obese weight range (48.5%), as well in women. There were no significant correlations between serum cortisol concentration and age both gender groups. While there were highly significant correlations between cortisol level and BMI, waist, and WHR (except in female subjects), also there were highly significant correlations between cortisol level and SBP,DBP (mmHg)only in male. In both groups, total cholesterol concentration, FBS, and A1C were significantly correlated with serum cortisol. Negatively correlated has been observed between serum cortisol and HDL-C in men but not in women. In men, the results of cortisol with CV risk factors (dyslipidemia, D.M, hypertension, at least 2 risk factors and three risk factors) show significant differences (p>0.0). In summary, there is a major association between cortisol levels, obese, and chronic diseases. These conclusions promote the hypothesis that the opposing effect of adiposity on the chronic diseases might be mediated by cortisol. This association could cause early development of cardiovascular diseases even in males.